Glutathione Transferase P1 Polymorphism Might Be a Risk Determinant in Heart Failure. (2nd June 2019) - Simeunovic, Dejan; Odanovic, Natalija; Pljesa-Ercegovac, Marija; Radic, Tanja; Radovanovic, Slavica; Coric, Vesna; Milinkovic, Ivan; Matic, Marija; Djukic, Tatjana; Ristic, Arsen; Risimic, Dijana; Seferovic, Petar; et al.
Abstract : Disturbed redox balance in heart failure (HF) might contribute to impairment of cardiac function, by oxidative damage, or by regulation of cell signaling. The role of polymorphism in glutathione transferases ( GSTs ), involved both in antioxidant defense and in regulation of apoptotic signaling pathways in HF, has been proposed. We aimed to determine whether GST genotypes exhibit differential risk effects between coronary artery disease (CAD) and idiopathic dilated cardiomyopathy (IDC) in HF patients. GSTA1, GSTM1, GSTP1, and GSTT1 genotypes were determined in 194 HF patients (109 CAD, 85 IDC) and 274 age- and gender-matched controls. No significant association was found for GSTA1, GSTM1, and GSTT1 genotypes with HF occurrence due to either CAD or IDC. However, carriers of at least one variant GSTP1 ∗ Val (rs1695) allele were at 1.7-fold increased HF risk than GSTP1 ∗ Ile/Ile carriers (p = 0.031 ), which was higher when combined with the variant GSTA1 ∗ B allele (OR = 2.2, p = 0.034 ). In HF patients stratified based on the underlying cause of disease, an even stronger association was observed in HF patients due to CAD, who were carriers of a combined GSTP1 (rs1695)/ GSTA1 "risk-associated" genotype (OR = 2.8, p = 0.033 ) or a combined GSTP1 ∗ Ile/Val+Val/Val (rs1695)/ GSTP1 ∗ AlaVal+∗ ValVal (rs1138272) genotype (OR = 2.1, p = 0.056 ). Moreover, these patients exhibited significantly decreased left ventricular end-systolic diameter compared to GSTA1 ∗ AA/ GSTP1 ∗ IleIle carriers (p = 0.021 ). Higher values of ICAM-1 were found in carriers of the GSTP1 ∗ IleVal+∗ ValVal (rs1695) (p = 0.041 ) genotype, whereas higher TNF α was determined in carriers of the GSTP1 ∗ AlaVal+∗ ValVal genotype (rs1138272) (p = 0.041 ). In conclusion, GSTP1 polymorphic variants may determine individual susceptibility to oxidative stress, inflammation, and endothelial dysfunction in HF.